تقيم صلاحية مياه الابار في شمال منطقة الناصريه للاستهلاك البشري والحيواني والزراعي - تركي محمد (University of Thi-Qar Journal of Science, 2010)
The study was conduct to investigate the suitability of wells water in northern of Al- Nasiryah city for drinking and agriculturing using through its study of the chemical ,physical and biological proprieties. The results showed that water of these wells unsuitable for human and animals from physical and chemical proprieties .Also these wells are bad for using it in agricultures purposes but is suitable for animals and polarity after treating it from high concentrations of sulfate , The study recommending use a new technology to purifications of water reverse osmoses before using water of this wells for different purposes.